Karang Taruna's Role in Youth Empowerment Through Sports and Skill Training Programs - Murdiono, Maskup; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
Background: Youth empowerment is vital for community progress, often facilitated by organizations like Karang Taruna. Specific Background: In Kalipecabean Village, Karang Taruna actively engages in youth activities, but its impact on empowerment remains unclear. Knowledge Gap: Limited studies focus on the role of Karang Taruna in this village. Aims: This study examines how Karang Taruna functions as a motivator, facilitator, and mobilizer in youth empowerment. Results: A qualitative analysis revealed that Karang Taruna conducts various activities, including sports competitions, training programs, and government collaboration, enhancing youth participation. However, challenges such as resource limitations and inconsistent engagement remain. Novelty: This study provides specific insights into Karang Taruna's multifaceted role in a village setting. Implications: Strengthening partnerships and diversifying programs could enhance the organization’s impact on community development. Highlights: Karang Taruna acts as a motivator by organizing activities to enhance youth participation. Collaboration with local government enables Karang Taruna to function effectively as a facilitator. Use of technology, like WhatsApp, assists Karang Taruna in its role as a mobilizer to engage youth in positive community activities. Keywords: Youth Empowerment, Youth Organization, Karang Taruna, Community Development, Facilitator